(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
The first case of COVID-19 in Bangladesh was declared in March 08, 2020 and since then we are fighting against this deadly pandemic under the prudent and dynamic leadership of Hon’ble Prime Minister Sheikh Hasina as Chief Advisor. The active, sincere and dedicated efforts of Prime Minister’s Office, Cabinet Division, Ministry of Health and Family Welfare and other different ministries have proved this COVID battle to be a winning game for our country. All the doctors, nurses and health workers played the pivotal role along with administration, police and all others. Among the frontline doctors, the fellows and members of all specialties of Bangladesh College of Physicians and Surgeons (BCPS) had a significant participation. They remain to be appraised. This review article probes to reveal the enormous contributions of all fellows and members of BCPS in various sectors of the COVID-19 battle in Bangladesh. This paper analyzed all activities of BCPS fellows and members by collecting data from the COVID-19 dedicated hospitals, Directorate General of Health Services, Bangladesh and directly from fellows of BCPS. A systematic search in the net was also performed using specific search words to extract relevant data and articles published on COVID-19 from Bangladesh. A non-probability sampling technique was used without any structured questionnaire. Data were directly included in MS excel spread sheet. Simple description analysis was performed and results were expressed in tables and charts. We found that fellows and members of BCPS took a significant leadership and provided supreme dedicated services in almost all fields of COVID-19 crisis; e.g. frontline patientcare, education and training, national policy making, research and publication and nationwide guidance and awareness build-up. Among the doctors of government COVID-19 dedicated hospitals in Dhaka, about 650 fellows participated in treating about 1.5 lacs admitted patients. First interim guideline on COVID-19 management in Bangladesh was published by fellows in executive committee of Bangladesh Society of Medicine. It was later transformed into national guideline by DGHS. Fellows were the leaders at national level. The National Technical Advisor Committee and Directorate General of Health Services of Bangladesh are the two main bodies who lead the war in the frontline and both are headed by fellows of BCPS. Journal of BCPS was the first in Bangladesh to publish COVID-19 supplement issue on July 31, 2020 with 12 original articles. So far 128 COVID related articles from BCPS fellows have been published in national and international journals. Fellows fought in the frontline in every sector, shoulder to shoulder with all doctors and health workers of Bangladesh. They have triumphed their beloved college, Bangladesh College of Physicians and Surgeons, to be one of the greatest centers of excellence for the medical education and patient care in Bangladesh. J Bangladesh Coll Phys Surg 2022; 40: 19-27